Probabilistic finite element model updating using Bayesian statistics : applications to aeronautical and mechanical engineering /: applications to aeronautical and mechanical engineering. (2017) - Marwala, Tshilidzi, 1971-; Boulkaibet, Ilyes, 1981-; Adhikari, Sondipon
No abstract available